0.5 V, high gain two-stage operational amplifier with enhanced transconductance. Issue 1 (2nd January 2018) - Bashir, Mudasir; Patri, Shreehari Rao; KrishnaPrasad, K. S. R.
ABSTRACT: An ultra-low-power, bulk-driven (BD) two-stage operational transconductance amplifier (OTA) operating in weak inversion region with enhanced transconductance is introduced. The aim is to boost the transconductance of OTA by using multiple current shunt auxiliary differential amplifiers in positive feedback through source degeneration circuits at input stage. The OTA employs a class AB amplifier at the output stage for high DC gain, while ensuring rail-to-rail operation. The overall OTA is realised in 180 nm complementary metal-oxide semiconductor standard process and its operation is validated through worst-case post-layout simulations at 0.5-V power supply. The OTA drives a maximum bias current of 48 nA achieving an open-loop DC gain of 78 dB, 1.6 μV/√Hz input referred noise at 1 kHz, total harmonic distortion of −66.35 dB and power consumption of 35 nW. The amplifier results in a remarkable improvement in slew rate, unity gain bandwidth and offers a transconductance of at least 10 times to that of conventional BD OTAs.